ANALISIS KEPUASAN PELANGGAN TERHADAP LAYANAN SHOPEE EXPRESS (SPX) MENGGUNAKAN KERANGKA ITIL V3 DOMAIN SERVICE OPERATION - Nurkamiden, Miyzah; Rahman, Ferosita W (TRANSFORMASI, 2025)
AbstractShopee Express (SPX) is an internal logistics service of the Shopee platform designed to improve the speed and quality of goods delivery. Although its presence provides added value, various complaints from users indicate that there are still shortcomings in its implementation. This research aims to evaluate customer satisfaction with SPX services using the ITIL version 3 framework, specifically in the Service Operation domain. The research approach used is descriptive quantitative by distributing questionnaires online to SPX users. The research focused on three main processes in Service Operation, namely incident management, request fulfillment, and access management. The research instrument was tested for validity and reliability using SPSS software. The test results showed that all statement items were valid and reliable. Furthermore, the data was analyzed to determine the level of service maturity. The findings show that all three subdomains are at maturity level 3 (Defined), which means that processes are documented and implemented regularly. Nonetheless, further evaluation and systematic improvement are still needed to achieve more optimal service quality.Keywords: Customer Satisfaction, Shopee Express, ITIL v3, Service Operation, Maturity LevelÂ Â